The efficacy of supplying supplemental cobalt, selenium and vitamin B₁₂ via the oral drench route in sheep - Williams, Joshua Robert; Williams, Nia Elizabeth; Kendall, Nigel R. (Elsevier, 2017)
Cobalt and selenium are essential trace elements required for ruminants. There are many different methods of supplementation available to sheep including boluses, in feed, free access minerals, pasture dressing and oral drenches. Recent changes in European legislation have resulted in a reduction in the maximum permitted level (MPL) of cobalt to be included in ruminant diets from 2 mg/kg at 88% DM to 1 mg/kg at 88% DM with a suggested supplementary rate of 0.3 mg Co/kg at 88% DM. This study aimed to determine the efficacy of cobalt plus/minus vitamin B₁₂ and selenium supplementation from oral drenching over a 13 day time period. Seven groups of grass silage fed Suffolk cross mule lambs (n=56) were randomly allocated to one of 7 treatments, a 5 ml oral drench containing 700, 2300, 12000 mg Co/l, with or without 2300 mg vitamin B₁₂/l in a factoral design, with an additional control group which received no drench. All drenches also contained selenium at 625 mg/l. Lambs were weighed on days 0 and 13. The lambs were sampled by jugular venepuncture on days 0, 1, 2, 3, 4, 5, 6, 7, 9, 11 and 13, with samples analysed for plasma selenium and cobalt by ICP-MS, erythrocyte glutathione peroxidase by colourimetric assay and vitamin B₁₂ by immunoassay. The results showed that cobalt via a drench was able to raise plasma cobalt in a dose dependent manner, with each dose level significantly higher than the previous level at all post drenching time points (P<0.05). However, the cobalt containing drenches did not significantly raise vitamin B₁₂ concentrations in the plasma. Vitamin B₁₂ containing drenches were able to elevate vitamin B₁₂ in the plasma for a period of 7 days (P<0.05). The selenium content of the drench was able to significantly raise the plasma selenium from day 1 throughout the rest of the trial (day 13) (P<0.001). A significant increase in erythrocyte glutathione peroxidase activity of the sheep did eventually occur at day 13 (P<0.05). In summary, the addition of vitamin B₁₂ via the drench route resulted in a short term elevation (7 days) of plasma vitamin B₁₂ concentrations whereas cobalt sulphate alone was unable to significantly raise vitamin B₁₂ concentrations within this trial in sheep with marginally adequate cobalt status, despite elevating plasma cobalt concentrations. The drench route was also able to elevate plasma selenium concentrations from a marginal selenium status.